Spatial econometrics using microdata - Dubé, Jean; Legros, Diego (London ISTE Ltd Hoboken, NJ John Wiley & Sons, Inc., 2014)
The objective of this book is to make a link between existing quantitative approaches... and the manner in which we can generalize thess approaches to cases where the available data for analysis have a spatial dimension.
Includes bibliographical references (pages 215-225) and index.
Keywords: Spatial analysis (Statistics) -- Data processing